PENERAPAN UNDANG-UNDANG NOMOR 13 TAHUN 2006 TENTANG PERLINDUNGAN SAKSI DAN KORBAN DENGAN UNDANG-UNDANG NOMOR 31 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG- UNDANG NOMOR 13 TAHUN 2006 DALAM PERLINDUNGAN WHISTLEBLOWER OLEH LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN - SIHOTANG, DEWI SARI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Amid the lack of legal protection in Indonesia, a whistleblower may be threatened because of reports or testimony of the alleged violations and crimes. The parties who feel aggrieved will most likely provide resistance to prevent whistleblower report or testimony. Not even rule out those who feel aggrieved can threaten and carry out reprisals. Until now there has been no legislation that specifically regulates the whistleblower in Indonesia. Based on this fact, then there are two formulation of the problem in writing this essay, namely: First, What are the weaknesses of Act No. 13 of 2006 on Protection of Witnesses and Victims of the protection afforded Institute Witness and Victim Protection Against Whistleblower so amended by Act No. 31 of 2014? Second, How Application of Law No. 31 of 2014 on the Amendment of Act No. 13 of 2006 in the Whistleblower Protection By Witness and Victim Protection Agency?This research is a normative research, because this research author directly discusses the principles of law and its comparison. Source data used are secondary data sources comprising: primary legal materials, secondary law and tertiary legal materials. Data collection techniques in this study was conducted in accordance with methods of assessment literature or documentary studies.From the analysis of the problems that can be concluded first, Weaknesses Act No. 13 of 2006 on the Protection of Witnesses and Victims of the protection afforded by the Witness and Victim Protection Agency Against Whistleblower whistleblower is a limitation defisini understanding includes the notion of the reporting and the reporting offenders. Second, the adoption of Act No. 31 of 2014 on the Amendment of Act No. 13 of 2006 on the Protection of Whistleblower By Institute for the Protection of Witnesses and Victims are applying on the definition of the reporting (whistleblower) in the explanation of the Law Institute of witness protection, strengthening of authority Lermbaga Witness and Victim Protection; the expansion of the subject of protection; expansion of services to victims and witness protection, increased cooperation and coordination between the protection of witnesses and victims, rewards and special treatment given to the perpetrator Witness, witness Reporting (Whistleblower). From the above analysis the authors suggest, first, the whistleblower should receive adequate protection from the competent institutions. Second, it requires the existence of a law that specifically regulates the Whistleblower.Keywords: Application - Protection - Witness and Victim - Whistleblower